Career paths of 1988 and 1998 nurse graduates in Switzerland: nurses at work pilot study. (20th March 2017) - Addor, V.; Jeannin, A.; Schwendimann, R.; Roulet Jeanneret, F.
Abstract : Aim: To investigate career paths and nurses' reasons to quit their job in Switzerland. Background: Increasing the duration of employment is the most efficient measure to reduce the worldwide nursing shortage. The results of the pilot phase for the retrospective cohortnurses at work study are presented. Methods: In 2012, 1085 graduates' names of two test‐cohorts (1988 and 1998) from 26 Swiss nursing schools were asked to complete a web‐based questionnaire. A snowball method was applied to recruit their graduate mates, together with advertisements through employers, study partners and a press release. Results: The overall participation rate was 26.5% ( n = 287). The median duration of employment in nursing was 23 and 14 years, respectively, and 80% of the potential employment time was spent within nursing. Half of the respondents reported they had left a sector of care, or nursing altogether, at least once, for personal choices, work–family conflict, heavy schedules, high workload, underused skills, lack of participation in decision‐making or unsupportive nursing management. Conclusion: Most Swiss‐trained nurses were still employed in nursing 24 and 14 years after graduation, respectively, with a third having worked part‐time periods. Implications for nursing management: Provisional retention recommendations are provided, which will be tested in the full study with validated instruments.